DAMPAK BULLYING TERHADAP MORTALITAS PADA PELAJAR; ANALISIS BERDASARKAN DEMOGRAFI SOSIAL DAN KARAKTERISTIK INDIVIDU - Nisrina Aulia Rahmani; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study analyzes the impact of bullying on student mortality by considering social demographic factors and individual characteristics. The literature review shows that bullying contributes to an increased risk of suicide, mental disorders, and a decline in students' quality of life. Social demographic factors such as gender, age, and socioeconomic background influence the level of mortality risk. Females are more often victims of verbal violence, while males are more often perpetrators of physical violence. Low socioeconomic status also increases vulnerability to the negative effects of bullying. Individual characteristics such as stress levels, depression, and anxiety, as well as lack of social support and weak stress-coping abilities, are associated with an increased risk of mortality in students. Addressing bullying requires a comprehensive approach involving education, effective school policies, parental involvement, and adequate psychological support to create a safe and supportive learning environment. This study highlights the need for awareness of the serious impact of bullying on student well-being and the importance of appropriate interventions to protect the younger generation from its negative consequences.